Discussants - Co-Pierre Georg; Daniel Opolot; Michael Rose (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This study is the first to examine the role of discussants in academic knowledge production. Comparing articles of similar quality with andwithout discussants,we find that having a discussant increases a paper's probability of publication in prestigious journals, but not its citation count. Conditional on having a discussant, citation count and probability of publication in a prestigious journal increase in the discussants' prolificness. This supports the existence of a quality channel through which discussants improve the inherent quality of a paper. Conversely, we do not find evidence for the existence of a diffusion channel whereby papers garner more citations because discussants diffuse information about the paper within their social network.
Keywords: A14; D83; G00; 330; Discussants; Intellectual collaboration; Academic Impact; NBER Summer Institutes